Edukacja nie na próżno. Rzecz o (nie)świadomej tożsamości osób niepełnosprawnych intelektualnie - Ramik-Mażewska, Irena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
Education is a complex process. Very often it is defined as a general set of action aimed at education, which comprised of aims and rules. Exemplification of education are educational institutions, and educational programmes on each its level. Among many of its aims the most crucial is leading the individual to full independence. Independence is a complex process, demanding not only the example but also own and very often verified experiences. Experiences, which allow the individual to recognize own possibilities, needs and roles, which are going to be fulfilled. Independence allows then for asking questions concerning oneself, own place among others, and these always stay in a close bond to own identity. In special education the subject of identity gain greater significance. Pedagogues concentrate mainly on language expression and on actions, by which disabled are expressing themselves. More important become examining if undertaken educational actions allow disabled to perceive themselves as independent individuals. Are they equipped with emancipated, inner strategies of controlling? Or, another way round, is their independence controlled from outside and depends on retrieving inner patterns of behaviours?